PENGGUNAAN MODEL PEMBELAJARAN PEMBERIAN TUGAS DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN SENI BUDAYA SISWA KELAS XI SMAN 10 KOTA PEKANBARU (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2015)
But the problems that appear in the learning process of cultural arts subjects inclass XI SMAN 10 Pekanbaru City today is still dominated by the activities of the teacher,because the methods used so far are not able to generate gaerah and interest students learnsome vital lessons so that students become passive and just accept material from the teacheralone, as well as less attractive in art education lesson, resulting in low student learning outcomes,in the year 2013/2014 ketuntasasan student learning on the subjects of art education is 60 thisis due to the teacher only using means or methods of lecture and question and answer only indelivering course material.Based on the description above problems, need to find a solution. The solution is to change thelearning strategy through Classroom Action Research (CAR) by using the method of grantingduty.That the application of learning methods giving the task to improve learning outcomes ofstudents of class XI SMAN Pekanbaru. The increase can be seen in the following aspects:1. Summary of teachers increased every meeting on the first cycle of the first meeting of 62.50%and 72.50% second meeting, the first meeting of the second cycle of 80.00% and 87.50% secondmeeting. Student activity also increased every meeting on the first cycle of the first meeting of60.00% and 70.00% second meeting. At the first meeting of the second cycle increased 77.50%and 85.00% second meeting.2. Results of study before action with an average value of 57.60. After the action in the firstcycle increased the average value becomes 66.08 and increased in the second cycle with a meanvalue of 75.43 ratamenjadi.3. Complete the classical increased from a base score 6 students (26.08%) who completedincreased by 34.79% to 14 students (60.87) in the first cycle, then increased again by 30.44% to21 the students (91.30%) in the second cycle.Keywords: Learning method of assignment, learning outcomes.